Increase the foliage area of Asparagus Officinalis L. Cv. UC 157 F1 “asparagus” by the spraying of Gibberellin (AG3) and 6 – Benzilaminopurine (6 – BAP) - Paraguay, José (2010)
The present work had as objective to study the increment of the leaf area of Asparagus Officinalis L., for they were used it asparagus crown with 5 yolks, to those that were applied by aspersion, different concentrations of the hormones of gibberellic acid and 6-bencilaminopurina which were applied at the 25, 60, 110 and 160 days respectively. It was found that in the different rehearsed treatments one doesn't observe differential significant in the increment of the number of plants, plant height, number of yolks and dry weight of foliage. However it was observed that the combined application of the phytohormonas in the range of 0.110 at 0.230 m of gibberllic acid and 0.037 to 0.075 m of 6-Bencilaminopurin a bigger number of yolk is achieved (13%), sprout (7%), plant height (11.3%) and dry weight (7.3%) in the treated plants. Concluded to continue making studies of sinergism of these two phytohormonas, gibberellic (AG3) and 6-bencilaminopurina (6-BAP), seeking to achieve adequate levels of leaf area increase of the leaf area in the asparagus.